THE COMPONENTS OF ADAPTIVE LEARNING ENVIRONMENT FOR COMPUTER-ORIENTED LESSONS ﻿ (Journal of Information Technologies in Education (ITE), 2012)
The issues of adaptive computer-oriented learning environment for visual impaired children are discussed in this article. The author proposes techniques for making of adaptive environment components. These components depend of individual characteristics of pupils.
Keywords: adaptive learning environment; computer-oriented lessons; visual impaired children